Elevating Vocational Student Competence: The Crucial Need for English Literacy Competence - Simanjuntak, Marudut Bernadtua; Rafli, Zainal; Utami, Sintowati Rini (SCAD Independent, 2025)
This study aims to explore the role of reading competence in English literacy for vocational students, focusing on its impact on human resource management and the effectiveness of public learning organizations. The method used is a descriptive qualitative literature review to identify the required competence levels, basic literacy needs, and the urgency of developing effective reading skills in preparation for entering the job market. The results show that reading competence goes beyond basic literacy and includes understanding technical materials, specific industry documents, and job-related texts, all of which are crucial for successful navigation in chosen fields as well as the development of critical thinking and problem-solving skills. This study also highlights the fundamental needs of vocational learners, including access to educational resources aligned with their field of expertise, and adequate language support programs for various levels of English proficiency. This research recommends enhancements to vocational curricula, professional development for educators, language support programs, and collaboration between vocational institutions and employers. The implications of this study confirm that reading ability is not merely a skill but a strategic necessity for vocational success that enhances job eligibility and adaptability, as well as supporting growth in human resource management and public learning organizations.